2009
DOI: 10.1002/pssc.200982146
|View full text |Cite
|
Sign up to set email alerts
|

Meeting challenges in nanomaterials for sustainable energy applications using high‐resolution positron methods

Abstract: Positron methods are promising as in‐situ depth‐resolved probes for the study of the (electronic) structure of semiconductor nanocrystals embedded in active thin layers of future generation solar cells, and of metal hydride thin films with applications as hydrogen sensors and hydrogen switchable mirrors. The (time‐resolved) evolution of the positron‐electron momentum distribution is presented, associated with two sintering steps observed upon heating pyridine‐capped CdSe nanocrystal films in a vacuum. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…The change in S-parameter is similar in magnitude as for the Mg to MgH 2 transformation in Mg [5][6][7] and Mg 0.90 Ti 0.10 films [7]. Our previous studies [5,15] demonstrated that such a large reduction in S-parameter is a direct result of the metal-insulator transition upon hydrogenation to the MgH 2 phase. Mg metal, namely, has a freeelectron-like electronic structure with a Fermi momentum cut-off at p F ∼ 5.3 × 10 −3 m o c [5], leading to a relatively sharp valence electron momentum distribution (EMD) [5].…”
Section: Doppler Depth Profiling Of Metal Hydride Thin Filmssupporting
confidence: 52%
See 2 more Smart Citations
“…The change in S-parameter is similar in magnitude as for the Mg to MgH 2 transformation in Mg [5][6][7] and Mg 0.90 Ti 0.10 films [7]. Our previous studies [5,15] demonstrated that such a large reduction in S-parameter is a direct result of the metal-insulator transition upon hydrogenation to the MgH 2 phase. Mg metal, namely, has a freeelectron-like electronic structure with a Fermi momentum cut-off at p F ∼ 5.3 × 10 −3 m o c [5], leading to a relatively sharp valence electron momentum distribution (EMD) [5].…”
Section: Doppler Depth Profiling Of Metal Hydride Thin Filmssupporting
confidence: 52%
“…2) show similar clear and large shifts upon hydrogenation, typical for the Mg to MgH 2 metal-to-insulator transition [5,15]. In Refs.…”
Section: Double Layer Behavior Of Mg 90 Ti 10 H X Filmsmentioning
confidence: 58%
See 1 more Smart Citation
“…The transition from the free-electronlike Mg metal to the insulator metal hydride phase leads to a substantial broadening of the electron momentum distribution. 15 A remarkable feature of the S-W diagram is that the cluster points for Mg 70 Ti 30 and Mg 90 Ti 10 lie very close to those of well-annealed ͑defect-free͒ Mg and of sputterdeposited Mg layers. 10 Despite the high Ti-fractions of up to 30%, the cluster points remain surprisingly far from the S-W point of well-annealed Ti.…”
mentioning
confidence: 81%
“…10 The S-W cluster point characteristic for the metal Mg 70 Ti 30 phase shows a clear and large shift to the S-W point for the fluorite Mg 70 Ti 30 H x phase upon hydrogenation of the layer. Our previous studies 10,15 demonstrated that such a large reduction in S-parameter is a direct result of the metalinsulator transition occurring during the transition from the Mg to the MgH 2 phase. The transition from the free-electronlike Mg metal to the insulator metal hydride phase leads to a substantial broadening of the electron momentum distribution.…”
mentioning
confidence: 95%